Emerging Ethical Perspective in Physician-Patient Relationship - Raina, Rangeel Singh (J Clin Diagn Res, 2014)
Traditional health systems, with patients as passive recipients of care, have proven unsuccessful in stemming the most irresistible and exponential growth of the epidemic we now face. There is considerable healing power in a good Physician-patient relationship. In the field of healthcare, patient empowerment has been acknowledged as an alternative to compliance in order to guide the provider–patient relationship. It will help patients’ confusion, fear and doubt slowly transform into clarity, relief and assurance. With the positive role of physicians, patients will definitely be relieved of hopelessness, have higher satisfaction, better adherence and improved health. There is no doubt that this small gesture by physicians will be a precious gift to humanity.